Taxation of Swedish firm owners: The great reversal from the 1970s to the 2010s - Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2017)
By the late 1960s, real effective taxation of income from individual firm owner-ship in Sweden approached 100 percent. A series of tax reforms initiated in the late 1970s reversed this situation. This paper has a threefold purpose: (1) to elucidate the thinking behind the vision of creating a largely market-based system without wealthy capitalists and how that vision guided the design of the tax system; (2) to outline and evaluate the numerous changes in the tax code made since the late 1970s, the empirical and intellectual basis of these changes, and the implications of these changes for the taxation of individual firm ownership; and (3) to compare the size of the largest individual wealth holdings in the mid-1960s to their equivalents in the 2010s and discuss in what sense and to what extent the general public's views have changed regarding sizeable individual income streams and wealth derived from business activity. Today, the tax code favors already wealthy individuals. By contrast, high labor income taxation combined with a high valuation of existing assets renders wealth accumulation difficult for persons with no initial wealth.
Keywords: H20; H32; L26; N44; 330; Owner-level taxation; Entrepreneurship; Institutions; Sweden; Tax policy